Prospects for Establishment of Technological Complexes in Machine Building Industry on The Basis of Electromechatronic Propulsion Systems; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Osipov Yu. M. Yury Mirzoevich (Innovative technologies for producing and testing permanent joints in mechanical engineering, 2015)
Title screen